Vision in Ehlers-Danlos syndrome. Role of orthoptics - Claude Hamonet; Lucette Ducret (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2022)
Ehlers-Danlos disease, usually called Ehlers-Danlos syndrome, is an inherited connective tissue disorder that spares the central nervous system except in its connective component. It is manifested by a set of symptoms and clinical signs which are the expression of the connective tissue's frailty. Visual manifestations are explained by tissue's fragility and proprioception disturbance increased by muscle dysfunctions: cornea's fragility, photophobia, diplopia, blepharospasms, eyelids' retractions, myopia, and astigmatism. The orthoptist's role is to help in the prescription of prism correction rather than rehabilitation, which is ineffective. In combination, global effect treatments, in particular for dystonia, and dysautonomia... is essential in this frequent disease, poorly described and therefore very seldom diagnosed. It is transmitted to all the children of an affected person. The objective of this work is to contribute to the diagnosis of Ehlers-Danlos disease more often and more frequently in affected families. The orthoptist's role is very important because the correction of diplopia has functional consequences. Pine-hole glasses may give some relief by filtering out the light that dazzles these patients significantly.